EDUKASI PENYULUHAN KANTIN SEHAT DAN PENGELOLAAN KEUANGAN BAGI YAYASAN PENDIDIKAN ISLAM DIPONEGORO - Safira, Safira; Rachmawati, Annisa Noor; Aini, Rukmi Nur; Wati, Galuh Rachma; Pradita, Bagas (STIE Atma Bhakti, 2024)
Community service activities in the form of assistance in education and counseling of the healthy canteen of the Diponegoro Islamic Education Foundation and its financial management. The benefits that participants can obtain from this PPM activity include providing information to teachers, committees and employees about the importance of providing healthy food and having nutritional content that is appropriate for the needs of each age of consumers and how to manage their finances. Community service activities were carried out in the hall of the Diponegoro Islamic Education Foundation using lecture and discussion methods. To determine the effectiveness of the participant counseling activities, participants were invited to discuss and given questions. Based on the results of the discussion, it was found that there was an increase in the knowledge of the counseling participants regarding nutritious food sources, which were avoided and important to consume and the canteen knew how to manage its finances properly and correctly. Keywords: Healthy Canteen, Nutrition Counseling, and Health Education